African Americans and Depression: The Development of a Culturally Competent Depression Scale for Reducing Treatment Disparities - B. R. Kennedy (Issues and Development in Health Research Vol. 2, 2021)
African Americans suffer depression for a longer period than their White counterparts. Often, African Americans are misdiagnosed and under-treated in the conventional healthcare system. Research studies reported the symptoms of depression among African Americans are inconsistent with the DSM-V. Previous Depression scales have not been culturally competent reflecting the depression symptoms of African Americans. This chapter address the treatment disparities in African Americans and the need for more culturally competent depression scales. The researcher developed a depression scale to reflect the racism and psychosocial factors contributing to depression in African Americans. African Americans are less likely to receive consistent quality care and evidence-based treatment guidelines (i.e., medication therapy or psychotherapy) and less frequently included in research studies. Tools for assessing depression need to be culturally sensitive. Also, healthcare professionals need to be aware of cultural factors when conducting assessments and obtaining a medical history and physical. When prescribing psychotropic medications, clients need adequate assessment and an accurate diagnosis to receive the appropriate medication. Also, clients need an accurate diagnosis when providing culturally competent therapy. If depression is adequately identified in African Americans, health providers will accurately diagnose depression and provide culturally competent treatment.